Household Income Structure and Electrical Appliance Ownership: Evidence from Japanese National Household Survey - Matsumoto, Shigeru (International Journal of Energy Economics and Policy, 2016)
Earlier research examined how total household income determines appliance ownership. However, this study uses micro data from the Japanese National Survey of Family Income and Expenditure to examine how income structure and wealth determine the number of appliances in a household. Household income structure does affect appliance ownership: though non-labor income lowers the likelihood of dishwasher ownership, labor income raises it. Wives’ incomes and non-labor income increase the number of TVs while a husband’s income decreases it. Appliance ownership is predominantly determined by housing conditions. Households owning a detached house have more appliances, though more frequently install solar water heaters. Keywords: Appliance ownership; Household Income Structure; Micro data JEL Classifications: D12; D13; Q41